Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1093/jpids/pis036
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Abnormalities Among HIV-Exposed, Uninfected Infants: IMPAACT Protocol P1025

Abstract: The overall frequency of laboratory SAEs was low and decreased with age. Preterm infants are at higher risk of hemoglobin- and total lymphocyte count-related SAEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Pacheco et al reported significantly decreased infant hemoglobin and neutrophil values, and Mussi-Pinhata et al described anemia at hospital discharge in 24% of ARV-exposed infants, although in both studies nearly all AE were of grade 1 or 2 [ 17 , 23 ]. Read et al described grade ≥3 anemia or neutropenia in less than 10% of ARV-exposed infants in the first six weeks of life [ 19 ]. Four infants in our study required a blood transfusion due to anemia, all of whom were born at ≤32 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Pacheco et al reported significantly decreased infant hemoglobin and neutrophil values, and Mussi-Pinhata et al described anemia at hospital discharge in 24% of ARV-exposed infants, although in both studies nearly all AE were of grade 1 or 2 [ 17 , 23 ]. Read et al described grade ≥3 anemia or neutropenia in less than 10% of ARV-exposed infants in the first six weeks of life [ 19 ]. Four infants in our study required a blood transfusion due to anemia, all of whom were born at ≤32 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The SMARTT arm of the Pediatric HIV/AIDS Cohort Study (PHACS) is currently ongoing and aims to estimate the incidence of conditions and diagnoses potentially related to in utero exposure to ARVs or exposure in the first 2 months of life among children born of HIV-infected mothers. Another recent study of over 1500 HIV-exposed infants and uninfected infants exposed to ARVs and to trimethoprimin-sulfamethoxazole in utero and in early infancy demonstrated that serious adverse events related to hemoglobin, absolute neutrophil count, total lymphocyte count, and glucose were experienced by fewer than 10% of infants in the first 6 months of life [12]. Although these results are encouraging, it is clear that further pharmacokinetic, efficacy, and safety data are needed for these medications in pregnancy as well as for exposed infants.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were similar to those reported for the IMPAACT P1025 study, where 91% of infants received ZDV alone as neonatal prophylaxis, 3% also received SD NVP, and 6% received other combination ARV prophylaxis. 22 However, infants in the United States are much less likely to receive combination prophylaxis than their European counterparts, where up to 14% receive combination prophylaxis. 5,8 In addition, only about 2% of infants in our evaluation received a three-drug combination prophylaxis regimen, while use of triple-ARV prophylaxis is relatively common in Europe and Canada.…”
Section: Discussionmentioning
confidence: 99%